EXTH-27. ACTIVATING THE IMMUNITY WITHIN THE TUMOR USING VIROIMMUNOTHERAPY: DELTA-24-RGD ONCOLYTIC ADENOVIRUS ARMED WITH THE IMMUNOPOSITIVE REGULATOR GITRL. (11th November 2019) - Rivera-Molina, Yisel; Fueyo, Juan; Jiang, Hong; Nguyen, Teresa; Ho Shin, Dong; Youssef, Gilbert; Fan, Xuejun; Gumin, Joy; Alonso, Marta M; Phadnis, Sheetal; Lang, Frederick; Gomez-Manzano, Candelaria
Abstract: Based on promising results of recent clinical trials using oncolytic viruses, virotherapy is evolving as an alternative to treat patients with malignant glioma. Our group developed the oncolytic adenovirus Delta-24-RGD (DNX-2401) that is being tested, alone or in combination with anti-PD1, in clinical trials for recurrent glioblastoma (NCT00805376; NCT01956734; NCT02798406). The results suggest that, besides the expected oncolytic effect, the injection of the pathogen initiated, in a subset of patients, an anti-tumoral immunity that led to 20% of long-term survivors (3.5–5 years). To further enhance this effect, we have armed Delta-24-RGD to express the co-stimulatory ligand GITRL, and generated Delta-24-GREAT. The intracranial injection of Delta-24-GREAT prolonged the survival of GL261 glioma-bearing immunocompetent mice when compared to Delta-24-RGD treatment ( P =0.002, log-rank test). Delta-24-GREAT treatment resulted in enhanced frequency of tumor-infiltrating lymphocytes: T lymphocytes (CD45 + /CD3 + ) and cytotoxic T lymphocytes (CD45 + CD3 + CD8 + ). Functional studies performed by culturing splenocytes from Delta-24-GREAT-treated mice with glioma cells and analyzing secretion of Th1 cytokines, such as IL2 and IFN-γ, showed that lymphocytes recognized not only viral antigens but also tumoral antigens, suggesting the triggering of anti-tumoral immunity. Of interest, Delta-24-GREAT treatment resulted in an antigen-restricted anti-tumor memory effect and in the generation of central immune memory. Thus, rechallenging the survivor mice from the first experiment with a second implantation of glioma cells did not lead to tumor growth, and we detected an increased frequency of central memory CD8 + T cells (CD45 + CD62L + ). However, survivor mice developed lethal tumors when implanted intracranially with B16/F10 melanoma cells, strongly indicating that the developed immune response was specific for GL261 glioma antigens. This is a novel approach using an oncolytic adenovirus expressing GITRL to target cancer and to stimulate the immunity within the tumor. Our data strongly indicate that this type of strategy may be further developed to treat patients with malignant glioblastoma.